Unique roles of co-receptor-bound LCK in helper and cytotoxic T cells - Horkova, Veronika; Drobek, Ales; Paprckova, Darina; Niederlova, Veronika; Prasai, Avishek; Uleri, Valeria; Glatzova, Daniela; Kraller, Markus; Cesnekova, Michaela; Janusova, Sarka; Salyova, Eva; Tsyklauri, Oksana; et al. (Nature Immunology, 2023)
The kinase LCK and CD4/CD8 co-receptors are crucial components of the T cell antigen receptor (TCR) signaling machinery, leading to key T cell fate decisions. Despite decades of research, the roles of CD4–LCK and CD8–LCK interactions in TCR triggering in vivo remain unknown. In this study, we created animal models expressing endogenous levels of modified LCK to resolve whether and how co-receptor-bound LCK drives TCR signaling. We demonstrated that the role of LCK depends on the co-receptor to which it is bound. The CD8-bound LCK is largely dispensable for antiviral and antitumor activity of cytotoxic T cells in mice; however, it facilitates CD8+ T cell responses to suboptimal antigens in a kinase-dependent manner. By contrast, the CD4-bound LCK is required for efficient development and function of helper T cells via a kinase-independent stabilization of surface CD4. Overall, our findings reveal the role of co-receptor-bound LCK in T cell biology, show that CD4- and CD8-bound LCK drive T cell development and effector immune responses using qualitatively different mechanisms and identify the co-receptor–LCK interactions as promising targets for immunomodulation.
CRIS-Team Scopus Importer:2023-01-13